Comparison of coping methods in marital disputes and the communication pattern of couples in married women with and without borderline personality - Gharavi, Sara; Anasseri, Mehryar (Psychology of Woman Journal, 2023)
Objective: Numerous studies indicate the existence of fears, tensions, legal conflicts and traumatic interpersonal relationships and their subsequent low quality of life in patients with borderline personality. The purpose of this research was to compare the ways of dealing with marital disputes and the communication pattern of couples in married women with and without borderline personality. Method: The current research was a causal-comparative study and the participants were selecting by random available sampling method in Qom city in 2018, including 100 subjects and 50 individuals for each group, and among them, Leichsenring’s borderline personality questionnaire (1999), Revised Conflict Tactics Scale (CTS-2, 2004) and Communication Patterns Questionnaire (CPQ, 1984) were distributed. The obtained data were analyzed with SPSS software and univariate analysis of variance. Results: There was a significant difference between the marital discord scales and couples’ communication patterns in women with and without borderline personality, with 99% confidence. Based on the obtained data, the components of the scale of marital disputes (injury, sexual abuse, verbal abuse, physical violence, mental violence) and the scale of couples’ communication patterns in women with and without borderline personality, showed more than 47% of the effect, in women with and without borderline personality. Conclusion: The results showed that self-learning variables marital intimacy and job satisfaction positively and significantly affect marital adjustment.